Development Problems of Business Structures in the Context of Transformation - Yulia VERTAKOVA; Maria KLEVTSOVA; Yulia POLOZHENTSEVA; Alexandra CHULAKOVA (Communications of International Proceedings, 2020)
The practical experience of foreign countries shows that the formation and development of partnerships between enterprises has a positive effect on the modernization of the economy and the harmonious development of the business environment. The transition to the knowledge economy and the stimulation of innovation require rethinking of the role of interaction between business structures in the field of small entrepreneurship. However, since there is a wide variety of tasks, goals, activities and business conditions for the participants in the relationship, it is important to study the process of interaction between business structures in the field of small business. The purpose of the article is to analyze the development problems of business structures in the context of transformation. As a methodological basis for the study, the authors used the methods of comparative, statistical and graphic-analytical analysis of the main indicators of the development of business structures. The study analyzes the dynamics of key indicators of the development of business structures in Europe and Russia, which makes it possible to assess the impact of small and medium-sized businesses on the economic development of countries. On the basis of the comparative analysis, the key problems in the development of small and medium-sized businesses in foreign countries have been identified. The programs of public and private financing of business structures in Russia and abroad have been analyzed. Measures to support and regulate the activities of business structures have been summarized, which allows taking into account the peculiarities of the functioning of small and medium-sized businesses in various economic spheres.
Keywords: Transformation; Small Business; Government Regulation